Quantitative proteomic analysis of the tizoxanide efect in vero cells (2020)
Nitazoxanide (NTZ) is efective against helminths and numerous microorganisms, including bacteria and viruses. In vivo, NTZ is metabolized into Tizoxanide (TIZ), which is the active circulating metabolite. With the emergence of SARS-Cov-2 as a Pandemic agent, NTZ became one of the molecules already approved for human use to engage clinical trials, due to results in vitro showing that NTZ was highly efective against the SARS-Cov-2, agent of COVID-19.There are currently several ongoing clinical trials mainly in the USA and Brazil involving NTZ due not only to the in vitro results, but also for its long-known safety. Here, we study the response ofVero cells toTIZ treatment and unveil possible mechanisms for its antimicrobial efect, using a label-free proteomic approach (LC/ MS/MS) analysis to compare the proteomic profle between untreated- andTIZ-treated cells. Fifteen diferentially expressed proteins were observed related to various biological processes, including translation, intracellular trafcking, RNA processing and modifcation, and signal transduction.The broad antimicrobial range ofTIZ points towards its overall efect in lowering cell metabolism and RNA processing and modifcation.The decreased levels of FASN, HNRNPH and HNRNPK with the treatment appear to be important for antiviral activity.